TBLA: Implementation of PjBL and Student Collaborative Skills in Science Learning at MTs Muhammadiyah 1 Malang - Sri Wahyuni; Iin Hindun; N. Nurwidodo; Ravena Puspitasari; M. Mashuri (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2024)
Teachers are required to develop professional learning that can produce qualified students. Consequently, a learning model is required that enables 21st-century abilities. Each individual is supposed to master skills in the form of 21st century skills, one of which is collaboration. The Project-Based Learning (PjBL) is chosen with the consideration that it has stages that are able to encourage students to collaborate with other group members, use various thinking abilities of students individually and in groups, and improve the quality of interaction between students. This study aims to describe the implementation of learning and student collaborative skills, to describe TBLA in science learning at MTs Muhammadiyah 1 Malang, particularly in Vertical Motion material. This research method was qualitative descriptive research. The objects of study were 25 teachers and 8th-grade students of MTs Muhammadiyah 1 Malang. The research stages included designing teaching modules by using PjBL learning, implementing learning, and reflecting on learning based on the lesson study stages that consisted of a Plan Do See. The results of the study indicate that the implementation of PjBL in science learning, consisting of 6 steps, namely drawing questions, compiling project plans, compiling schedules, monitoring, testing results, and evaluating experiences, have been well described, both narratively and visually in the learning. Student collaboration skills in science learning material Vertical motion are 73.4% (high category). TBLA shows that the teacher speeches are more dominant, namely 85.94% and the students are 14.05%. It can be concluded that the implementation of PjBL learning was carried out well and students' collaborative skills were in the high category.